2018
DOI: 10.1017/s003329171800017x
|View full text |Cite
|
Sign up to set email alerts
|

Distinct risk factors for obsessive and compulsive symptoms in chronic schizophrenia

Abstract: BackgroundObsessive-compulsive disorder (OCD) is common in clozapine-treated patients although the actual prevalence, phenomenology and risk factors remain unclear. The aim of the present study was to address the three aforementioned questions.MethodsThe electronic records of a large cohort of clozapine-medicated schizophrenia patients routinely screened for OCD were used. The Obsessive Compulsive Inventory Revised version (OCI-R) was available from 118 cases and a 21 points cut-off threshold for OCD was defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
33
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 45 publications
7
33
0
3
Order By: Relevance
“…It is of note that we covered the prevalence and complex phenomenology of obsessions and compulsions in clozapine-treated patients in a previous work (Fernandez-Egea et al, 2018). Here, we use the term OCD to define these phenomena, albeit acknowledging the open debate about its pathophysiology and correct terminology.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is of note that we covered the prevalence and complex phenomenology of obsessions and compulsions in clozapine-treated patients in a previous work (Fernandez-Egea et al, 2018). Here, we use the term OCD to define these phenomena, albeit acknowledging the open debate about its pathophysiology and correct terminology.…”
Section: Methodsmentioning
confidence: 99%
“…Routine clinical assessments are described elsewhere (Fernandez-Egea et al, 2018) and include full psychiatric history, comprehensive mental state examination, current medication list, smoking habit, legal and illegal drug history, early life history, clozapine treatment length and side effects assessment and physical health assessment. Among others, psychopathological scales included assessment for general functioning [Global Assessment of Functioning (GAF)](Haro et al, 2003), short version of the Warwick-Edinburgh Wellbeing Scale [SWEWBS](Brown et al, 2016) and symptom severity using the Clinical Global Impression (CGI) for Schizophrenia (Busner and Targum, 2007) which includes 5 domains (positive, negative, cognitive, and depressive) rating from 1 to 7 for absence to extreme severity.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Age, gender, marital status, and education level did not show a significant difference between the 3 groups, which was consistent with most of the previous studies. 3,4 On the other hand, some studies reported a significant relationship between the sociodemographic variables and OCD presence in schizophrenia. 11 There was no significant difference between 3 groups in terms of the duration of schizophrenia.…”
Section: Sociodemographicmentioning
confidence: 99%